Neutralizing the Tentacles of Organized Crime. Assessment of the Impact of an Anti-Crime Measure on Mafia Violence in Italy - Anna Laura Baraldi; Erasmo Papagni; Marco Stimolo (Fondazione Eni Enrico Mattei (FEEM), 2023)
Organised crime tightens its corrupting influence on politics through violent intimidation. Anti-crime measures that increase the cost of corruption but not of the exercise of violence might accordingly lead mafia-style organizations to retaliate by resorting to violence in lieu of bribery. On the other hand, this kind of anti-crime measure might also induce criminal clans to go inactive, owing to the lower expected payoff from the "business" of influencing politics, which would reduce violence. To determine which of these possible effects is prevalent, we undertake an empirical assessment of the impact of city council dissolution for mafia influence in Italy as prescribed by Decree Law 164/1991 in discouraging violence against politicians in the period 2010-2019. Our difference-in-differences analysis shows that in the dissolved municipalities the enforcement of the Law reduces violence and that the effect persists (at least) for two electoral rounds. The most likely driving channel of this result is the renewed pool of politicians elected after compulsory administration. These findings are robust to a series of endogeneity tests.
Keywords: C25; D73; D78; I38; K42; 330; Organized Crime; Violence; Anti-corruption measures; Spillovers